Quantification of Tremolite in Friable Material Coming from Calabrian Ophiolitic Deposits by Infrared Spectroscopy - Antonella Campopiano; Angelo Olori; Annapaola Cannizzaro; Antonino Iannò; Pietro Paolo Capone (Journal of Spectroscopy)
The aim of this study is to identify the infrared absorption band suitable for quantifying tremolite in three powdered samples (fine, medium, and large size classes) coming from a quarry of ophiolitic friable rocks in the western part of the Calabria region of Italy. Three IR bands were considered: OH stretching band between 3700 and 3650 cm−1, the stretching bands of the Si-O-Si linkage between 1200 and 900 cm−1, and the absorbance band at 756 cm−1 attributable to tremolite. The amount of tremolite in the test samples was quantified by using the curve parameters of the three analytical bands. The quantitative analysis of tremolite using the band due to OH stretchings (3700–3650 cm−1) and the bands attributed to the Si-O-Si stretchings (1200–900 cm−1) showed high values for all test samples. Their use overestimated the tremolite amount because both bands were affected at the interfering mineral silicates such as talc, kaolinite, chlorite, and serpentinites. The abundant presence of antigorite in studied samples mainly in medium size class sample had a key role in our findings. The band at 756 cm−1 was not affected at the interfering minerals and can be used for quantitative analysis of tremolite in sample coming from ophiolitic deposits.